ACTIVE LEARNING AND LEARNING MOTIVATION: RECONSTRUCTION OF ISLAMIC RELIGIOUS EDUCATION LEARNING RESULTS - Siti Perwanti, Bondan; Aprilliantoni, Aprilliantoni (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2022)
The purpose of this study was to prove the effect of the active learning approach and learning motivation on the learning outcomes of Islamic Religious Education (PAI) subjects at Al Muslim Junior High School Tambun. The active learning approach and learning motivation help students understand Islamic Religious Education materials. The approach of this paper is quantitative. The research method used is a survey. This study uses data collection techniques using questionnaires and written tests using multiple regression test data analysis techniques. The instruments used in this study were questionnaires, written tests, and Islamic Religious Education learning activities. The results showed that there was a significant effect of the active learning approach and learning motivation together on the learning outcomes of Islamic Religious Education at SMP al Muslim Tambun in Bekasi Regency. This causal relationship is proven by Sig. = 0.000 < 0.05 and Fcount = 6.950, there is a significant effect of active learning approach on learning outcomes of Islamic Religious Education at Al Muslim Junior High School in Bekasi Regency. This is proven by Sig. = 0.020 <0.05 and tcount 2.399, and there is a significant influence of learning motivation on learning outcomes of Islamic Religious Education at Al Muslim Middle School Tambun in Bekasi Regency. This is proven by Sig. = 0.028 < 0.05 and tcount 2.248.